Multiple Solutions for a Sixth Order Boundary Value Problem - Martinez, A. L. M.; Pendeza Martinez, C. A.; Bressan, G. M.; Souza, R. M.; Stiegelmeier, E. W. (Trends in Computational and Applied Mathematics, 2021)
This work presents conditions for the existence of multiple solutions for a sixth order equation with homogeneous boundary conditions using Avery Peterson's theorem. In addition, non-trivial examples are presented and a new numerical method based on the Banach's Contraction Principle is introduced.